THE EFFECT OF DIFFERENT HARVEST TIMES ON POPULATION GROWTH AND BIOMASS OF WORMS(Tubifidae) - Rathi Syafni; Nuraini Nuraini; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe Research was conducted in August - October 2018 in the Outdoor Laboratory of Fish Hatchery and Breeding at the Faculty of Fisheries and Marine, University of Riau. The purpose of this research was find out the frequency of different harvest times for increase and  biomass of silk worms (Tubifex sp.). The research method used in this study was the experimental method, the experimental design used was a one-factor Completely Randomized Design (CRD) with 4 treatments and 3 replications which were discussed descriptively. Harvesting are sampling using ½ inch pipe with 20 points in each container. The composition of P14 harvesting treatment is 4 times 56 days. P21 harvesting 3 times 63 days. P28 harvesting 2 times 56 days. P56 harvesting 1 time 56 days. The highest treatment is at the frequency of harvest time 2 times 56 days with a population increase of 27,305 ind and biomass 81.01 g. Water quality parameters during the reseach were temperature 26-28oC, pH 6-7,5, dissolved oxygen 6.0-6,5 mg / l, water discharge 0,0044-0,024 L / sec.Key words: Tubifidae, Frequency, harvest time, population increase and biomass